Does unintended birth lead to zero dose of DPT vaccine among children aged 12–23 months in India? - Pritu Dhalaria; Pawan Kumar; Ajay Verma; Pretty Priyadarshini; Ajeet Kumar Singh; Bhupendra Tripathi; Arindam Ray (Human Vaccines & Immunotherapeutics)
Zero-dose children pose a key challenge in immunization programs due to their association with access to the health system and primary healthcare services. Examining zero-dose aids an in-depth understanding of healthcare disparities among children and caregivers. The disparity in utilization of maternal and child health services raises concerns about the potential consequences of unintended pregnancies on vaccine uptake. The National Family Health Survey 2019–21 (NFHS-5) served as the data source, and the study analyzed information from 43,247 children aged 12–23 months. Sociodemographic variables such as birth order, wealth quintile, gender, social group, religion, residence, mother education, and delivery-related factors were considered. Statistical analysis involved weighted estimates, chi-square tests, and multivariate multinomial logistic regression. The results show that 9.14% of children from unintended pregnancies were zero-dose for the DPT vaccine, compared to only 6.69% of children from intended pregnancies in India, indicating a higher prevalence of zero-dose associated with unintended pregnancies. The regression analysis shows the adjusted odds among children from an unintended birth − 1.21 times higher for the zero-dose DPT vaccine as compared to the intended birth (AOR: 1.21, 95% CI: 1.06,1.38). Zero-dose immunization has become a crucial metric of childhood immunization performance, gaining prominence in national agendas, the IA 2030 framework, and Gavi’s 2021–25 strategy. The study findings highlight a significant association between unintended pregnancy and zero-dose DPT vaccination. The results provide compelling evidence that unintended pregnancies could be a potential risk factor for zero-dose DPT vaccination in low- and middle-income countries.